1996
DOI: 10.1002/(sici)1097-4660(199609)67:1<84::aid-jctb525>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

By-products of Ethoxylation of Simple Alcohols in the Presence of Tripropylamine

Abstract: Ethoxylation of simple alcohols such as methanol, ethanol and butanol in the presence of tripropylamine, in addition to the main reaction products, results in by‐products from tripropylamine and ethylene oxide. This side‐reaction consumes tripropylamine, forming dipropylamine ethoxylates and alcohol ethoxylates. These compounds remain in the product and influence the commercial properties of alcohol oxyethylates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
5
0
2
Order By: Relevance
“…It is not caused by the presence of the volatile (bp 89 °C) triethylamine. The catalyst undergoes reaction with the alkylene oxide, and the intermediate product, (CH 3 CH 2 ) 3 N + CH 2 CH 2 O − , undergoes Hofmann elimination 11. 12 …”
Section: Resultsmentioning
confidence: 99%
“…It is not caused by the presence of the volatile (bp 89 °C) triethylamine. The catalyst undergoes reaction with the alkylene oxide, and the intermediate product, (CH 3 CH 2 ) 3 N + CH 2 CH 2 O − , undergoes Hofmann elimination 11. 12 …”
Section: Resultsmentioning
confidence: 99%
“…Quando se utilizam aquelas aminas como catalisador na etoxilação de álcoois de baixa massa molecular observa-se que, mesmo não possuindo o "hidrogênio ativo", a concentração de R 3 N no meio diminui ao longo do tempo. A concentração de tripropilamina pode cair de 1,3% (m/m) na mistura reacional inicial para 0,3% após um período de 2 h e 30 min de reação 61 , mesmo quando a massa total da mistura permanece aproximadamente constante. Se esse tempo for estendido para 8 h, a concentração de tripropilamina cai ainda mais significativamente para 0,001%.…”
Section: Catálise Básicaunclassified
“…Se esse tempo for estendido para 8 h, a concentração de tripropilamina cai ainda mais significativamente para 0,001%. Por outro lado, uma mistura reacional, após a destilação para a remoção do catalisador trietilamina (p. e. = 89 ºC), ainda apresenta atividade catalítica 62 61,62 . Nos experimentos, a formação desses subprodutos causou uma coloração marrom, provavelmente devido à presença de compostos de alto peso molecular 61 , o que comercialmente significa uma queda na qualidade dos produtos etoxilados, que são incolores.…”
Section: Catálise Básicaunclassified
“…Our earlier investigations revealed that the tertiary amine catalysts were also exposed to ethoxylation in the reaction mixture after their dealkylation. [1][2][3] The formed by-products are also amines and they keep on providing the catalytic activity for the basic process. In the case when N,N-dimethylaniline (DMA) is employed as a tertiary amine catalyst, the side reactions proceed as follows:…”
Section: Introductionmentioning
confidence: 99%